Amylin Receptor: A Common Pathophysiological Target in Alzheimer’s Disease and Diabetes Mellitus - Fu, Wen; Patel, Aarti; Jhamandas, Jack H. (Frontiers in Aging Neuroscience, 2013)
Amylin (islet amyloid polypeptide) and amyloid beta protein (Abeta), which are deposited within pancreatic islets of diabetics and brains of Alzheimer’s patients respectively, share many biophysical and physiological properties. Emerging evidence indicates that the amylin receptor is a putative target receptor for the actions of human amylin and Abeta in the brain. The amylin receptor consists of the calcitonin receptor dimerized with a receptor activity-modifying protein and is widely distributed within central nervous system. Both amylin and Abeta directly activate this G protein-coupled receptor and trigger multiple common intracellular signal transduction pathways that can culminate in apoptotic cell death. Moreover, amylin receptor antagonists can block both the biological and neurotoxic effects of human amylin and Abeta. Amylin receptors thus appear to be involved in the pathophysiology of AD and diabetes, and could serve as a molecular link between the two conditions that are associated epidemiologically.